PENGARUH HARGA SAHAM, VOLUME PERDAGANGAN SAHAM DAN VARIAN RETURN TERHADAP BID ASK SPREAD DI SEPUTAR PENGUMUMAN STOCK SPLIT (Studi pada Perusahaan yang Listing di Bursa Efek Indonesia Periode Tahun 2005-2011) - Ikrima Shobriati (Fakultas Ilmu Administrasi Universitas Brawijaya, 2013)
Knowledge of the bid ask spread is very necessary for investors especially who wish to achieve capital gains. As capital market participants, dealers are always trying to determine the bid ask spread is reasonable to consider certain events or other conditions with respect to the securities held. The players in the capital market is in need of information that could affect the rise and fall of stock prices, as this can affect the decision making of investors in buying or selling stocks. One of the corporate action information published in the capital market is stock split. This research is explanatory research with quantitative approach. The sample used in this study is that the stock-split firms listed on the Indonesia Stock Exchange in the period of 2005-2011 that using purposive sampling method. The sample in this study amounted to 40 companies. This hypothesis was tested using multiple linear regression. Results of the study explained that the variable stock prices, stock trading volume and return variance simultaneously have a significant effects on the bid ask spread F value 3.674 with a significant level of 0.021. Variable stock prices and trading volumes partially has a significant effects on the bid ask spread and has a t value of -2.785, -2.121 and a significance level of 0.008, 0.041, whereas the partial return variant variable has not a significant effects on the bid ask spread and has a t value of 0.058 and 0.954 significance level. Stock price variable is the most dominant variable affecting the bid ask spread because it has the highest beta value. Keywords : Stock Prices, Stock Trading Volume, Return Variance, Bid Ask Spread